Minat investasi saham pada mahasiswa Universitas Nasional: Literasi keuangan, motivasi, dan persepsi risiko - Prasetyo, Agus; Elwisam, Elwisam (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
The purpose of this research was to analyze the effect of financial literacy, motivation and also risk perception on stock investment interest among national University students class of 2019-2020. Where this research comes from primary data generated from the answers of respondents through the distribution of a questionnaire. Sampling in this studi as many as 105 respondents with accidental sampling method. The data analysis technique used in this study is the PLS or Partial Least Square approach using the WrapPLS 7.0 application. Based on the results of the research the has been done, it is known that financial literacy, motivation, and risk pepception have a positive and significant influence on investment interest in National University students class of 2019-2020.